Fixed Point Results via Real-Valued Function Satisfying Integral Type Rational Contraction - Naveen Mani; Amit Sharma; Rahul Shukla (Abstract and Applied Analysis)
In this article, we mainly discuss the existence and uniqueness of fixed point satisfying integral type contractions in complete metric spaces via rational expression using real-valued functions. We improve and unify many widely known results from the literature. Among these, the work of Rakotch (1962), Branciari (2002), and Liu et al. (2013) is extended. Finally, we conclude with an example presented graphically in favour of our work.